The Relationship Between Market Sentiment Index and Stock Return Rates: An Analytical Study of the Iraq Stock Exchange (TANMIYAT AL-RAFIDAIN, 2025)
Investor sentiment is one of the destabilizing factors in the stock market, and measuring it is one of the main pillars of behavioral finance at global stock exchanges in general and Arab stock exchanges in particular. Therefore, the research sought to measure the behavioral biases of investors, specifically their sentiment as an indicator to express the sentiment of the financial market and as the primary determinant of their investment decisions, in addition to diagnosing and testing its impact on the monthly returns of the Iraq Stock Exchange for the period (1/1/2016 - 10/1/2024) in an attempt to answer the question, "Does market sentiment leave a clear impact on the rates of stock returns in the Iraq Stock Exchange?" By applying Principal Component Analysis (PCA) to construct the Investor Sentiment Index (SENT) according to a set of variables (trading volume, turnover rate, market value, and number of traded shares) in addition to some controlling macroeconomic factors, and using linear and non-linear regression analyses, the results confirmed the negative linear effect relationship between the sentiment index and market returns. No apparent nonlinearity in this relationship was observed, and the lack of impact of controlling economic factors is due to political risks and liquidity.
Keywords: Behavioral finance; investor sentiment; market sentiment; PCA analysis